ANALISIS USES AND GRATIFICATION DALAM MENENTUKAN STRATEGI DAKWAH - Mahfudlah Fajrie (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2015)
There are several theories of mass communication, one that needs to be developed in the process of propaganda are the uses and gratification theory (usability and satisfaction). Uses and gratification theory in mass communication is no longer look at the influence of the media on audiences, but what the audience of the media, this theory explains how individuals use mass communication to meet their needs. So audiences active against the media because of necessity. Audiences use media to fulfill expectations, and active audiences to select media and media content to satisfy his needs. So a good strategy and effective propaganda is to determine the use and selection of media to be used as well as propaganda material appropriate suit the needs of the community because the community uses and gratification theory or audiences which will determine the positive or not the propagation is done.